Sobre a luz e o silêncio : o plano de longa duração e a dinâmica do som no cinema de Carlos Reygadas - Reis, Hugo Leonardo Castilhos dos (2014)
This work aims to discuss the cinema of Carlos Reygadas, with the focuses on the importance of sound and its dynamics within the long duration take, a procedure that strongly characterizes the style of this director. Initially, excerpts from films Japón (2002), Battle in Heaven (2005) and Silent Light (2007) were analyzed to highlight the formation of a stylistic corpus and a predominantly contemplative and sensory conception of cinema. Then we elected Silent Light as a conductive thread of a broader analysis in relation to the main crop. Therefore, we had as main references studies by David Bordwell (2008) on traditional directors of the plan-sequence, as well as the categories and theoretical assumptions of Michel Chion (1994, 2009) on the uses of sound in cinema.